The Accounting and Analytical Reflection of Financial and Economic Risks in Housing Construction - Voskresenska Tetiana І. (Bìznes Inform, 2023)
The article discloses the peculiarities of occurrence of financial and economic risks in housing construction. It is examined that financial and economic risks in housing construction accompany the entire construction process – from the moment of obtaining permits to commissioning of housing construction objects. It is specified that financial and economic risks in housing construction affect the interests of all construction participants (investors, developers, intermediaries, buyers). It is noted that certain types of financial and economic risks, such as the currency and inflation ones, are inherent and arise for all participants in housing construction. Another part of the financial and economic risks arises for a separate subject of housing construction. In the process of housing construction, some types of financial and economic risks disappear, others, on the contrary, arise in accordance with changes in the primary conditions for housing construction. In order to reduce the negative effects of financial and economic risks, construction participants try to manage them through procedures such as: risk avoidance, risk sharing, and risk insurance. It is specified that the basic document, which provides for the possibility of a kind of insurance against the possibility of certain types of financial and economic risks for certain subjects of housing construction, is a construction contract. The peculiarities of reflection in the accounting of insurance and self-insurance by participants in housing construction of possible consequences of financial and economic risks in housing construction are disclosed. It is proposed to reflect insurance costs as part of deferred expenses with their gradual reflection in current costs, as well as in financial expenses (without prior reflection as deferred expenses). When using the mechanism of self-insurance by construction participants, the possible consequences of financial and economic risks reflect the creation of an insurance reserve and its write-off. The study emphasizes that owing to the impossibility of a clear identification of financial and economic risks, there is a problem of their accounting and analytical reflection by housing construction participants.